Memurnikan Mahkamah Konstitusi - Muhammad Iwan Satriawan; Mukhlis Mukhlis (SASI, 2018)
This study will focus discuss to changes in the authority of the constitutional court in indonesia. That since given authority decide a dispute the outcome of an election both at the central and local the constitutional court as if stuck to the award political reasons and there are several judge involved a corruption scandal decisions dispute the outcome of an election . So the establishment of judicial special election into a the substance of things not cleared by the formation of function constitutional court (M.K) as a squire the constitution where whose main duty is interpret the act. This research uses the method juridical normative by comparing function m.k in some countries and how the application of ideal in Indonesia.